(untitled) (Bangladesh Journal of Botany, 2021)
The relationship between the fungal community characteristics and soil environmental factors of volcanic ecosystem in Wudalianchi, China were investigated. The soil fungal community structure and diversity of new, old, and non-erupting volcanos were explored through highthroughput sequencing technology. The result showed that the physical and chemical properties of three plots were significantly different. Through sequencing 578 species, 366 genera, 202 families, 89 orders, 32 classes, and 11 phyla were detected. Among them Ascomycota and Basidiomycota were the dominant fungi phyla. The relative abundance of various flora determined by phylum classification showed significant differences. The Shannon, Simpson, Ace, and Chao1 indices for the soil fungi in the three plots were also significantly different. Redundancy and correlation analyses showed that the α diversity of fungi was significantly correlated with pH, organic matter and total nitrogen in the soil. These results indicate that soil environmental factors influence the fungal diversity in the different volcanic ecosystems in Wudalianchi, China. Bangladesh J. Bot. 50(2): 327-334, 2021 (June)